Submillimeter ionoacoustic range determination for protons in water at a clinical synchrocyclotron. (18th August 2017) - Lehrack, Sebastian; Assmann, Walter; Bertrand, Damien; Henrotin, Sebastien; Herault, Joel; Heymans, Vincent; Stappen, Francois Vander; Thirolf, Peter G; Vidal, Marie; Van de Walle, Jarno; Parodi, Katia
Abstract: Proton ranges in water between 145 MeV to 227 MeV initial energy have been measured at a clinical superconducting synchrocyclotron using the acoustic signal induced by the ion dose deposition (ionoacoustic effect). Detection of ultrasound waves was performed by a very sensitive hydrophone and signals were stored in a digital oscilloscope triggered by secondary prompt gammas. The ionoacoustic range measurements were compared to existing range data from a calibrated range detector setup on-site and agreement of better than 1 mm was found at a Bragg peak dose of about 10 Gy for 220 MeV initial proton energy, compatible with the experimental errors. Ionoacoustics has thus the potential to measure the Bragg peak position with submillimeter accuracy during proton therapy, possibly correlated with ultrasound tissue imaging.